Does the Attention of the Chinese Government Influence Chinese Nutrition, Exercise, and Health? Based on the Content Analysis of the Central Government Work Reports From 1978 to 2020 - Zhang, Wenpeng; Zhou, Yuomei; Li, Jingzhan; Zeng, Tingting; Liao, Jinlian (Frontiers in Nutrition, 2021)
The attention of the Chinese government on nutrition, exercise, and health refers to the attention degree of the Central Government to the nutrition, exercise, and health of Chinese nationals and reflects whether Central Government attach importance to Chinese nationals' nutrition, exercise and health or not and the distribution of resources, which influence the physical quality and health level of Chinese nationals. Based on the attention theory and attention distribution proposed by Herbert Simon, Dai Kai, et al., this study took 43 Central Government Work Reports from 1978 to 2020 as research samples, used literature reviews, and textual analysis methods, and applied the Nvivo12.0 software to conduct qualitative and quantitative analyses about the contents of the Central Government Work Report concerning the nutrition, exercise, and health of Chinese nationals. This research found the following: (1) There has been a relatively huge overall change in the attention of the Central Government, that is, the level of attention, to the nutrition, exercise, and health of Chinese nationals from 1978 to 2020, and the policies related to nutrition, exercise and health of Chinese nationals issued by the Central Government have been growing faster. (2) The income level of the urban and rural residents, the total production of various types of food, dietary structure, the total number of medical and health institutions, the average life expectancy of the Chinese population, and the number of sports venues have been constantly increasing since the reform and opening up, which has effectively promoted the improvement of the nutrition, exercise and health level of Chinese nationals, and it cannot be achieved without the attention and support of the Central Government. However, the change in the lifestyle of Chinese nationals has led to the growth of the modern “Civilization Disease,” which is also an important issue that the Central Government needs to handle urgently.